Effects of high-volume voluntary feed consumption on growth and health of Brown Swiss calves: Continued dam's milk feeding versus early introduction of milk replacer during the first week of life - Anton M. Vorndran; Julia Steinhoff-Wagner (Journal of Dairy Science)
ABSTRACT: Understanding nutritional needs and management during the neonatal period is crucial for reducing mortality rates and improving the overall health of calves, thereby impacting the economic viability of farming operations. Therefore, this study aimed to evaluate performance differences between calves fed dam's milk or milk replacer (MR) at high milk allowances during their first week of life. Twenty Brown Swiss calves (both male and female) were fed their dam's colostrum and transition milk for the first 6 feedings twice daily in unlimited amounts. They were then randomly assigned to 1 of 2 treatments: receiving either their dam's milk or MR for 8 consecutive feedings, twice daily in unlimited amounts. The calves were weighed 3 times during the experiment, and growth differences were visible at the end of the trial, with milk-fed calves exhibiting superior growth compared with MR-fed calves. Differences were also observed in fecal consistency, with MR calves showing higher occurrence of loose feces. Calves fed with dam's milk exhibited greater weight gain and a greater relative increase in BW, achieving a 22% increase compared with a 15% increase in MR-fed calves, both relative to their birth weight. The differences were explained by a higher nutrient density of dam's milk during the first week of life compared with MR, which, upon feed transition, decreased the daily consumed energy by 30% for MR-fed calves, without changing feed consumption. The higher feces scores were interpreted as a multifactorial issue likely caused by an abrupt change in feedstuff, higher concentrations of osmolality-influencing agents such as lactose and minerals, or a lack of abomasal clotting for high-volume MR-fed calves. Our findings demonstrate that Brown Swiss calves fed with dam's milk during their initial week of life exhibited superior growth performance, fewer health impairments, and improved fecal consistency compared with calves transitioned early and abruptly to MR. In order for MR to better imitate dam's milk during this early stage of life, lower lactose and lower ash but higher fat inclusion should be considered by manufacturers.